Integrasi Teknik Moderasi dalam Evaluasi Pembelajaran Sains Kafah di UIN Mataram NTB, Indonesia - A, Syahrial; Rokhmat, Joni; Ramdani, Agus; Hakim, Aliefman; Sukarso, AA (Kappa Journal, 2023)
The quality of teacher learning is a major concern in education. Moderation techniques are expected to contribute to improving the quality of teacher learning. Kafah science learning is a thorough learning, prospective teacher students get actual competence for one concept taught. These competencies include religion, science, application and meaningfulness. This research aims to integrate moderation techniques in kafah science learning to improve the quality of learning. The goal will be achieved by conducting experimental research with a one group pretest-postest design. The study involved 38 prospective PGMI UIN Mataram teacher candidates and a lecturer as a research sample. The quality of kafah science learning is measured using kafah science learning observation sheets. Learning observation is carried out by 3 observers to ensure the implementation of learning. Data on critical thinking skills were analyzed descriptively and statistically. The results show that the integration of moderation techniques in kafah learning can improve the quality of learning carried out by lecturers